The Physical and Mechanical Properties of Branch Wood of Schizolobium amazonicumDucke - Yusup Amin; Ika Wahyuni; Teguh Darmawan; Wahyu Dwianto; Sunarko Sunarko (Masyarakat Peneliti Kayu Indonesia, 2011)
One of the efficiency use of wood resources can be done by promoting the utilization of lesser-known species. However, high demand of familiar woods such as teak, kamper, meranti, mahoni, albizia, and acacia wood has limited the utilization of lesser-known species. The main purpose of this research was to determine the physical and mechanical properties of the branch-woodof Schizolobium amazonicum Ducke, one of lesser-known and a fast-growing species, and had recomonded its utilization. The physical and mechanical properties tested on this research were wood density, dimensional stability, Modulus of Elasticity (MOE), Modulus of Rupture (MOR), and compression strength parallel to grain. The sample testing refers to British Standard (BS 373, 1957). The result shows that the branch-wood of S.amazonicum has physical and mechanical properties as well as other fast-growing species, e.g. albizia wood. According to its density and MOR values, the S. amazonicum is classified as strength class of IV-III and it is possible used for light construction, furniture and plywood raw material.Key words: lesser known species, physical and mechanical properties, Schizolobiumamazonicum, strength class.